2021
DOI: 10.21037/atm-20-7482
|View full text |Cite
|
Sign up to set email alerts
|

Autocrined leptin promotes proliferation of non-small cell lung cancer (NSCLC) via PI3K/AKT and p53 pathways

Abstract: Background: Circulating leptin can directly act on tumor cells. However, a recent meta-analysis showed that plasma leptin concentration had no significant effect on the survival of lung cancer patients. So does Leptin have an effect on lung cancer? Or there may be other factors that influence the effect.Methods: Genome sequencing database Oncomine was searched to learn the differential expression of leptin between tumors and normal lungs. Fresh tumor specimens and paired normal lung tissue from six lung adenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
1
21
1
Order By: Relevance
“…The reverse transcription kit was purchased from Thermo Fisher. It was operated according to the user guide of the fluorescence quantitative kit, U6 and GAPDH were taken as internal parameters, and the relative content of PI3K/Akt/mTOR in CRC was calculated by using the 2 -△△Ct method ( Wang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse transcription kit was purchased from Thermo Fisher. It was operated according to the user guide of the fluorescence quantitative kit, U6 and GAPDH were taken as internal parameters, and the relative content of PI3K/Akt/mTOR in CRC was calculated by using the 2 -△△Ct method ( Wang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…At present, academic circles believe that the accelerated progress of CRC is caused by PIK3CA gene mutation of the PI3K/Akt/mTOR signal pathway and the loss of expression of phosphatase and tensin homolog deleted on chromosome 10 (PTEN). PIK3CA mutation is closely related to the location, degree of tissue differentiation, and immunohistochemical type of CRC lesions ( Zhihang Chen et al, 2020 ; Li et al, 2021 ; Wang et al, 2021 ; Jing Zhang et al, 2021 ). Cells carry out biological activities through proliferation, migration, invasion, and apoptosis, as well as cancer cells ( Xie et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In NSCLC, the PI3K/AKT/mTOR pathway has been heavily implicated in both tumorigenesis and the progression of disease (30,31). Previous studies have shown that the expression of PI3K, AKT and mTOR upregulated in NSCLC (31,32). The preclinical studies showed that AKT activation attributed to loss of PTEN, EGFR, PIK3CA mutation or HER2 amplification in NSCLC cell lines (29,33).…”
Section: Discussionmentioning
confidence: 99%
“…The authors, by investigating a total of 12,643 subjects, 4172 lung cancer cases, and 8471 controls, aged 35 to 74 years, from four cohort studies in the USA, Europe, China, and Singapore, found a statistical association between BMI and lung cancer risk both in current smokers (Odd Ratio, OR for overweight group: 0.79, 95% CI: 0.68-0.92, and obese group: 0.75, 95% CI: 0.60-0.93), former smokers (overweight group: 0.70, 95% CI: 0.53-0.93, and obese group: 0.55, 95% CI: 0.37-0.80), and lifelong non-smokers (overweight group: 0.77, 95% CI: 0.59-0.99, and obese group: 0.71, 95% CI: 0.44-1.14) [21]. Interestingly, levels of leptin, a major obesity-related adipokine, have been documented to positively correlate with non-small cell lung cancer (NSCLC) [22][23][24][25]. On the contrary, it has also been demonstrated that central or visceral adiposity, measured by visceral fat index (VFI), is associated with decreased recurrence-free and overall survival (OS) in lung cancer patients.…”
Section: Lung Cancermentioning
confidence: 99%
“…Leptin induced lung cancer cell proliferation by the activation of the PI3K/AKT/mTOR signaling pathway and through down-regulation of the P53 signaling pathway [25]. (iii) Leptin deletion induced a reduced cell growth and apoptosis in non-small-cell lung cancer (NSCLC) cell lines partially involving the Notch and JAK/STAT3 signaling pathways [156].…”
Section: Adipokinesmentioning
confidence: 99%